Mortality in polymyalgia rheumatica: a 38-year prospective population-based cohort study from Southern Norway - Stig Tengesdal; Øyvind Molberg; Øyvind Holme; Jan Tore Gran; Geirmund Myklebust (Arthritis Research & Therapy)
Abstract Background Robust long-term mortality data on patients with polymyalgia rheumatica (PMR) are lacking. The aim of this study was to determine all-cause mortality in isolated PMR using a large, population-based, inception cohort followed prospectively over a 38-year period. Methods Between 1987 and 1997, 337 incident cases of PMR and biopsy-proven GCA were included in a prospective, population-based inception cohort in Aust-Agder County, Norway. Diagnosis was ascertained clinically by a rheumatologist, with PMR cases meeting Bird`s criteria. Patients were followed until death or end of study on December 31st, 2024. Each case was matched by gender, age at inclusion, and residency with 15 population comparators drawn from the population registry in Norway. We assessed mortality and survival by standard mortality ratios (SMR) and the Kaplan-Meier method. Results A total of 274 patients with isolated PMR (66.1% female, mean age at diagnosis 71.9 years) and 63 patients with GCA (76.2% female, mean age at diagnosis 71.6 years) were included. By the end of the study, 96.4% of all patients were deceased. Mean follow-up time for all patients was 13.7 years, with a maximum of 35.3 years. For cases with isolated PMR, the overall SMR was 0.97 (95% confidence interval [CI] 0.85, 1.09), for men 0.77 (95% CI 0.62, 0.95), and for women 1.11 (95% CI 0.95, 1.28). For GCA, the overall SMR was 1.10 (95% CI 0.85, 1.40), with no gender difference. Conclusions In this comprehensive long-term follow-up study with nearly complete data on mortality, isolated PMR was not associated with increased mortality, reinforcing the view that it does not confer a higher mortality risk.